Potensi Pengembangan Produk Pembiayaan Akad Salam Di Bank Wakaf Mikro Al-Ihya Baitul Aqof Cilacap - Mutia Pamikatsih; Elok Ainur Latif (Universitas Yudharta Pasuruan, 2020)
The micro-agriculture sector is considered not bankable, which makes farmes look for sources of capital from the pengijon system. BMW aims to provide access to capital for the small community as well as provide guidance to micro-entrepreneurs. Based on the results of research on the salam contract, micro waqfbanks will help solve problems faced by farmers and micro waqf banks can maximize their role in community empowerment, especially the poor who are categorized economi cally active working poor and lower income communities. __________________________________________________________________ Sektor pertanian mikro dianggap tidak bankable sehingga membuat petani mencari sumber pemodalan dari sistem pengijon. BMW bertujuan menyediakan akses modal bagi masayarakat kecil serta melakukan pembinaaan kepada pelaku usaha mikro. Berdasarkan hasil penelitian akad salam pada bank wakaf mikro akan membantu menyelesaikan permasalahan yang dihadapi oleh petani dan Bank wakaf mikro dapat memaksimalkan perannya dalam pemberdayaan masyarakat, terutama masyarakat miskin yang berkatagori economically active working poor dan masyarakat lower income